1947
DOI: 10.1017/s0022029900004908
|View full text |Cite
|
Sign up to set email alerts
|

347. The disinfection of contaminated metal surfaces with hypochlorite solutions

Abstract: With 1 Plate, 1 Text-figure and 6 Charts)The work described here was designed to determine the value of hypochlorites as disinfectants for dairy utensils and the extent to which they could safely be used to replace steam and boiling water under wartime conditions.The general results of our findings and their bearing on the methods of applying hypochlorites have already been published with tentative methods for the use of sodium hypochlorite on the farm(i, 2). Some of the evidence for the statements in these pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1949
1949
1984
1984

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Furthermore the fact that satisfactory results can be obtained by the use of the full treatment once a day, and by a simplified treatment in the evening (Clegg, 1955), commends the efficacy of the method. Subsequently, arguments for and against the combined process have been mado by Swartling It is of course well known that the germicidal activity of hypochlorite solution is less under alkaline than under neutral or slightly acid conditions in the laboratory (see Johns, 1934;Costigan, 1937), but in tests designed to simulate practical use, this appeared not to be the case (Cousins & Wolf, 1946; Neave & Hoy, 1947). The latter workers experimenting with dried milk films on stainless steel trays and comparing the efficiency of hypochlorite solutions adjusted with different buffers to pH 7 and 11, showed that not only was the film more readily removed by solutions of higher pH but generally these were more germicidal.…”
Section: Chemical Disinfection In the Milk House And Parlourmentioning
confidence: 99%
“…Furthermore the fact that satisfactory results can be obtained by the use of the full treatment once a day, and by a simplified treatment in the evening (Clegg, 1955), commends the efficacy of the method. Subsequently, arguments for and against the combined process have been mado by Swartling It is of course well known that the germicidal activity of hypochlorite solution is less under alkaline than under neutral or slightly acid conditions in the laboratory (see Johns, 1934;Costigan, 1937), but in tests designed to simulate practical use, this appeared not to be the case (Cousins & Wolf, 1946; Neave & Hoy, 1947). The latter workers experimenting with dried milk films on stainless steel trays and comparing the efficiency of hypochlorite solutions adjusted with different buffers to pH 7 and 11, showed that not only was the film more readily removed by solutions of higher pH but generally these were more germicidal.…”
Section: Chemical Disinfection In the Milk House And Parlourmentioning
confidence: 99%
“…In tests involving the recovery of organisms from disinfectant treated surfaces, knowledge of the eaciency and reproducibility of recovery is desirable. Neave & Hoy (1947) in their studies of the disinfection of metal trays found that 'squeegeeing' the test surface in conjunction with a rinse solution was much more efficient than rinsing alone and removed twice as many organisms as a swabbing technique. They used a special long handled squeegee for experiments with 10-gal milk cans (Hoy & Neave, 1955).…”
Section: Survivors On Laboratory Test Surfacesmentioning
confidence: 99%
“…We have therefore tested a number of antiseptics by a method first suggested by our colleague Dr. W. D. Foster which is much more economical of time, glassware, and effort than the use of threads (Koch, 1881), garnets (Kr6nig andPaul, 1897), coverslips (Jensen and Jensen, 1933), glass slides (Johns, 1947), glass cylinders Mallmann andHaynes, 1945), or metal surfaces (Neave and Hoy, 1947;Stedman, Kravitz, and Bell, 1954).…”
mentioning
confidence: 99%